(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
This article talks about the history of music and its development, its origin, when and where it appeared, the role of Philharmonic societies (in the case of the Luxembourg Philharmonic), and the history of its development